2018
DOI: 10.14527/pegegog.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

The reflection of the attitudes and learning processes to learning environments with authentic tasks in life science class

Abstract: The purpose of this study was to determine the reflections of authentic task-based learning environments upon students’ learning processes and attitudes regarding the course of Life Science. In the study, which was designed in mixed model, the embedded experimental design was used. The study was carried out in an elementary school third-grade class and conducted in five weeks. The research data were collected via the Attitude Scale for Life Science Course, observations and video records, and semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…The positive effects of authentic learning on students' attitudes towards a course were also found in other studies. Accordingly, the positive effects of authentic learning activities on prospective teachers' attitudes towards the social service practice course were the finding obtained in Horzum and Bektaş (2012) whereas the positive effects of authentic learning activities on primary school students' attitudes towards the social studies course were the finding obtained in Gündoğan (2017). Thus, the findings obtained in this study may be said to be consistent.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The positive effects of authentic learning on students' attitudes towards a course were also found in other studies. Accordingly, the positive effects of authentic learning activities on prospective teachers' attitudes towards the social service practice course were the finding obtained in Horzum and Bektaş (2012) whereas the positive effects of authentic learning activities on primary school students' attitudes towards the social studies course were the finding obtained in Gündoğan (2017). Thus, the findings obtained in this study may be said to be consistent.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Life science is a lesson aiming to ease the child's adjustment to society and life and is nested in real life. As a result, in addition to this lesson providing students with essential life skills, it is to gain skills to help cope with adverse situations encountered in daily life (Gündoğan, 2017). It is considered very important to include work developing problem-solving skills in the design process for textbook activities.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the life science curriculum outcomes in terms of social skills (Gündoğan, 2017) showed that 1/3 of the results were related to social skills. However, the life science construct and vision have an entirely student-centered understanding (Tay & Baş, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Rule'ye (2006) göre otantik görevler gerçek yaşam problemlerini çözmek için öğrencilerin okulda öğrendiklerini kullanmalarına olanak sağlamaktadır. Bunun yanında otantik görevlerin gerçek yaşamda karşılaşılabilecek bir konu, sorun veya durumu konu edinmesi, tam tanımlanmamış olması, karmaşık olması, iş birliği ile çalışmaya olanak sağlaması, öğrencileri etkin kılması gerekmektedir (Gündoğan ve Gültekin, 2018;Young, 1993). Otantik öğrenmede otantik görevlerin verilmesiyle başlayan öğretim süreci, otantik etkinliklerle devam eder ve bu etkinlikler öğrencilerin problem çözme, eleştirel düşünme ve bilgi sentezleme gibi becerilerini gerçek hayata yansıtmalarına olanak sağlar.…”
Section: Introductionunclassified